Memes, monsters and the digital grotesque - Moreno Almeida, Cristina (Liverpool University Press, 2024)
Memes, Monsters, and the Digital Grotesque looks at the emerging and thriving new genre of digital horror from an innovative perspective. Examining digital cultural production during the period that has been referred to as the 'Arab Winter', Moreno-Almeida delves into the memes, animated cartoons, music videos, and expressive cultures — like fashion and urban subcultures — that emerged between 2016 and 2020. In revealing concealed narratives underlying the digital lives of artists, as well as ordinary people, Moreno-Almeida explores how memes, horror, and the grotesque capture a moment infused with political and affective significance, characterized by despair, alienation, and anomie, alongside opportunities for creative experimentation made possible in the postdigital era